2021
DOI: 10.48550/arxiv.2106.09042
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Implications of Eccentric Observations on Binary Black Hole Formation Channels

Michael Zevin,
Isobel M. Romero-Shaw,
Kyle Kremer
et al.

Abstract: Orbital eccentricity is one of the most robust discriminators for distinguishing between dynamical and isolated formation scenarios of binary black holes mergers using gravitational-wave observatories such as LIGO and Virgo. Using state-of-the-art cluster models, we show how selection effects impact the detectable distribution of eccentric mergers from clusters. We show that the observation (or lack thereof) of eccentric binary black hole mergers can significantly constrain the fraction of detectable systems t… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
23
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(23 citation statements)
references
References 91 publications
0
23
0
Order By: Relevance
“…The second and third columns provide the percentage of posterior support for 𝑒 10 > 0.1 and 𝑒 > 0.05 respectively. These two values are typical used as thresholds for 'detectable' binary eccentricity at 10 Hz using operational gravitational-wave detectors (e.g., Lower et al 2018;Samsing 2018;Rodriguez et al 2018b,a;Zevin et al 2019;Zevin et al 2021a), although the true threshold for eccentricity sensitivity is unique to each signal. The next two columns provide the natural log Bayes factors ln B for the hypotheses that 𝑒 10 β‰₯ 0.1 (0.05) against the hypothesis that 𝑒 10 < 0.1 (0.05).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The second and third columns provide the percentage of posterior support for 𝑒 10 > 0.1 and 𝑒 > 0.05 respectively. These two values are typical used as thresholds for 'detectable' binary eccentricity at 10 Hz using operational gravitational-wave detectors (e.g., Lower et al 2018;Samsing 2018;Rodriguez et al 2018b,a;Zevin et al 2019;Zevin et al 2021a), although the true threshold for eccentricity sensitivity is unique to each signal. The next two columns provide the natural log Bayes factors ln B for the hypotheses that 𝑒 10 β‰₯ 0.1 (0.05) against the hypothesis that 𝑒 10 < 0.1 (0.05).…”
Section: Resultsmentioning
confidence: 99%
“…In Zevin et al (2021a), the lower limit on this branching fraction, 𝛽 c , is shown to be 0.14 (0.27) at 95% credibility for a number of observations with 𝑒 10 β‰₯ 0.05, 𝑁 ecc = 1 (2), when the total number of observed BBHs is 𝑁 obs = 46.…”
mentioning
confidence: 94%
See 2 more Smart Citations
“…The physics of inspiral binaries is rich, including effects such as spin-induced precession [22,23], tidal interactions [24], and orbital eccentricity [25,26]. The simultaneous measurement of those effects is an important ingredient in discriminating between different black hole binary formation scenarios [27,28], and massive black hole binary evolution [29]. Efforts towards building waveforms for preccessing and/or eccentric waveforms have been carried out using various formalisms [23,[30][31][32][33][34][35][36].…”
Section: Introductionmentioning
confidence: 99%